Monitoring the micellar packing of photo-crosslinkable Pluronic F127 dimethacrylate during 3D printing - Bomediano, Mateus P.; da Silva, Laura C. E.; Mota-Santiago, Pablo; de Oliveira, Marcelo G.; Plivelic, Tomás S. (Frontiers in Soft Matter, 2024)
Pluronic F127 dimethacrylate (F127-DM) inks exhibit potential for 3D printing biomaterials due to their combined gelation and photo-crosslinking capabilities. Previous studies have explored their application in extrusion 3D printing of medical devices, relying on their long-range micellar ordering to impart mechanical stability, stretchability, and control over drug delivery. However, there is a lack of information regarding the impact of the extrusion and photo-crosslinking processes on the micellar ordering of F127-DM. Herein, we employed in operando synchrotron small-angle X-ray scattering (SAXS) to analyze the influence of various factors, including nozzle shape, nozzle size, extrusion rate, ink composition, and photo-crosslinking, on the micellar ordering of F127-DM. Our findings from 2D SAXS patterns indicate orientation of the micellar packing clusters along the flow direction. The nozzle diameter and shape emerged as crucial parameter, leading to increased disruption of long-range ordering with reduced anisotropy. Furthermore, 1D SAXS curves under UV-Vis light exposure revealed a partial preservation of the micellar packing structure, with cluster size reduction, and coexisting with randomly distributed micelles and unimers. These results underscore the importance of in operando synchrotron experiments for the systematic study of 3D printing parameters from a nanostructure perspective.